Adjunctive use of anti-inflammatory drugs for schizophrenia: A meta-analytic investigation of randomized controlled trials. (August 2019) - Cho, Myeongju; Lee, Tae Young; Kwak, Yoo Bin; Yoon, Youngwoo Brian; Kim, Minah; Kwon, Jun Soo
Objective: Recent evidence suggests that adjuvant anti-inflammatory agents could improve the symptoms of patients with schizophrenia. However, the effects of the adjuvant anti-inflammatory agents on cognitive function, general functioning and side effects have not yet been systematically investigated. The present meta-analysis aimed to explore the effects of anti-inflammatory agents in patients with schizophrenia comprehensively. Method: We performed a literature search in online databases, including PubMed, EMBASE and the Cochrane Database of Systematic Reviews. Randomized, placebo-controlled double-blind studies that investigated clinical outcomes including psychopathology, neurocognition, general functioning and extrapyramidal side effects were included. The examined anti-inflammatory agents included aspirin, celecoxib, omega-3 fatty acids, estrogen, selective estrogen receptor modulator, pregnenolone, N -acetylcysteine, minocycline, davunetide and erythropoietin. Results: Sixty-two double-blind randomized clinical trials studying 2914 patients with schizophrenia met the inclusion criteria for quantitative analysis. Significant overall effects were found for anti-inflammatory agents for reducing total, positive and negative symptom scores in the Positive and Negative Syndrome Scale. Cognitive improvements were significant with minocycline and pregnenolone augmentation therapy. General functioning was significantly enhanced by overall anti-inflammatory agents. There were no significant differences in side effects compared with placebo. Baseline total Positive and Negative Syndrome Scale score and illness duration were identified as moderating factors in the effects of anti-inflammatory augmentation on psychiatric symptom improvements. Conclusion: The comparative evaluation of efficacy and safety supported the use of anti-inflammatory adjuvant therapy over the use of antipsychotics alone. However, future studies could focus on patients with homogeneous clinical profile to figure out more detailed effects of anti-inflammatory therapy.